Review of the genus Argyresthia Hübner, [1825] (Lepidoptera: Yponomeutoidea: Argyresthiidae) from China, with descriptions of forty-three new species - Liu, Tengteng; Wang, Shuxia; Li, Houhun (Zootaxa, 2017)
The Chinese fauna of Argyresthia Hübner, [1825] included by 14 described species prior to this study. In the present paper we describe 43 new species and record seven species new to China. We also recognized six known Chinese species based on the available specimens; eight species previously reported for the fauna, but without available specimens for examination, are systematically placed in their relevant positions. The total species number of Argyresthia in China is brought to 64. The new species include: A. (Blastotere) aureola, sp. nov., A. (B.) sporadolepis, sp. nov., A. (B.) cineretra, sp. nov., A. (B.) affinicineretra, sp. nov., A. (B.) albaureola, sp. nov., A. (B.) densa, sp. nov., A. (B.) punctireticulata, sp. nov., A. (B.) dolichocoremata, sp. nov., A. (B.) longipenella, sp. nov., A. (Argyresthia) biloba, sp. nov., A. (A.) minutilepidota, sp. nov., A. (A.) flavifusca, sp. nov., A. (A.) trigonophylla, sp. nov., A. (A.) chiotorna, sp. nov., A. (A.) hirsuta, sp. nov., A. (A.) papillata, sp. nov., A. (A.) acuminata, sp. nov., A. (A.) curvativa, sp. nov., A. (A.) atomata, sp. nov., A. (A.) orthocera, sp. nov., A. (A.) cardiopetala, sp. nov., A. (A.) mala, sp. nov., A. (A.) longa, sp. nov., A. (A.) decurtata, sp. nov., A. (A.) minutisocia, sp. nov., A. (A.) scalprata, sp. nov., A. (A.) grammosacca, sp. nov., A. (A.) campylotropa, sp. nov., A. (A.) punctuata, sp. nov., A. (A.) chlorella, sp. nov., A. (A.) triangulata, sp. nov., A. (A.) subzonata, sp. nov., A. (A.) basistriata, sp. nov., A. (A.) longalbella, sp. nov., A. (A.) umbrina, sp. nov., A. (A.) umbrinistrigata, sp. nov., A. (A.) surrecta, sp. nov., A. (A.) lanosa, sp. nov., A. (A.) lata, sp. nov., A. (A.) cuprea, sp. nov., A. (A.) aurilata, sp. nov., A. (A.) convexa, sp. nov., and A. (A.) ellipsoidea, sp. nov. The newly record species include: A. (A.) pygmaeella ([Denis & Schiffermüller], 1775), A. (A.) retinella Zeller, 1839, A. (A.) angusta Moriuti, 1969, A. (A.) alpha Friese & Moriuti, 1968, A. (A.) beta Friese & Moriuti, 1968, A. (A.) kaoyaiensis Moriuti, 1982, and A. (A.) dislocata Meyrick, 1914. The male of A. (A.) trochaula Meyrick, 1938, and the male and female genitalia of A. (A.) aphoristis Meyrick, 1938 and A. (A.) dislocata are described for the first time. The misidentified species A. (A.) assimilis Moriuti, 1977 in China is described as A. (A.) mala, sp. nov. Argyresthia cryptomeriae Yang, nomen non rite publicatum, is validated as Argyresthia anthocephala Meyrick, 1936. Keys to the subgenera and to the Chinese species with available specimens are provided. Photos of adults and male and female genitalia are provided for all the examined species except two from Taiwan. Field photographs and biological information are provided where available. Five DNA barcode sequences of the two new species, A. (A.) surrecta, sp. nov. and A. (A.) lanosa, sp. nov., are provided for association of the sexes.